(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Objective The purpose of the current study was to evaluate the effect of Diode laser 650 nm, mineralized Nano-cellulose graft material, and their combination on bone healing using Masson’s Trichrome stain. Methods a total of 18 adult male white New Zealand rabbits were used. Two circular full cortical bone defects were drilled in each tibia, creating four bony defects in each rabbit, representing the four main groups of the study; group A (negative control), group B (filled with Tetramethyl pyridine oxyl “TEMPO” oxidized Nano-cellulose combined with Nano Amorphous-calcium-phosphate “nACP”, group C (combination group filled with experimental material and subjected to laser), group D (subjected to Diode laser 650 nm). In groups C and D, bony defects were subjected to laser irradiation during surgery, then repeated every other day for two weeks. Animals were sacrificed after two weeks and one month, histological samples were examined by Masson’s Trichrome stain. Results after two weeks, group D recorded the greatest mean area percent of osteoid, while group C recorded the lowest value. After one month, groups A and D showed full closure of the defects, groups B and C showed partial defect closure with retained bone graft material, with group B recording the greatest mean area percent of osteoid formation, whereas group C recorded the lowest value. Conclusion Diode laser biostimulation improved bone defects’ healing. Mineralized Nano-cellulose as a bone substitute showed a delayed effect in bone healing, and graft material resorption. The combination of LLLT with the mineralized Nano-cellulose material had no positive outcome on bone defect healing.